The effectiveness of trafficking in persons report in combatting human trafficking - Ab Hamid, Zuraini; Ab Aziz, Norjihan; Mohamad Amin, Noor Shuhadawati (OCERINT International Organization Center of Academic Research, 2017)
The Trafficking in Persons (TIP) Report is the main reference for countries around the world, particularly the United Nation state members, in determining their success in combatting human trafficking issues. The objective of the report is to fulfil three principal goals, namely to protect the trafficking victim, to prevent the crime, and to bring the perpetrator to justice. This report was initiated by the U.S. Department of State in 2001 as one of the efforts to monitor and increase worldwide efforts regarding the issues. As a destination and transit country for human trafficking, the U.S. Department of State has become the self-appointed country monitoring the human trafficking progress of (187) state governments since 2004. The first report for human trafficking that was published in 2001 stated that the related countries will be examined and placed either in Tier 1, Tier 2, or Tier 3 depending on their status. In order to be placed in the Tier 1 level, the government must fully comply with the minimum standards outlined in Section 108 of the Trafficking Victims Protection Act of 2000. If the government does not fully comply with the minimum standards for the elimination of trafficking, but has put significant efforts to comply with the standards, it is then placed in Tier 2. The failure for compliance by any governments would place it in Tier 3. Nevertheless, few issues are detected on the effectiveness of the TIP Report in the assessment of a country’s achievement in combatting the crime. The issues raised include (i) the monitoring body which is led by the U.S. Department of State; (ii) the 3P paradigm outlined by the Protocol to Prevent, Suppress, and Punish Trafficking in Persons Especially Women and Children which is heeded by the U.S. Department of State; and (iii) the assessment stipulated in the TIP Report which focuses too heavily on the protection of victims. To that end, this article studies the effectiveness of the TIP Report in assessing the countries involved, particularly Malaysia. Combining content analysis and semi-structured interview, this article argues that a lot of improvement must be done on the report’s transparency in assessing the countries and thus, proving its effectiveness in combatting the human trafficking issues.